An investigation on near-field and far-field characteristics of superheated ammonia spray. (15th September 2022) - Li, Shiyan; Li, Tie; Wang, Ning; Zhou, Xinyi; Chen, Run; Yi, Ping
Highlights: Intensity of near-field bubble explosion is quantified for superheated spray. Viscosity plays an important role in near-field bubble explosion. Superheat degree dominates near-/far-field characteristics of ammonia spray. Transient injection characteristics of high-pressure ammonia spray are investigated. 0-D model of tip penetration is established for superheated ammonia spray. Abstract: Ammonia is an attractive alternative fuel for internal combustion engines because it has an octane number above 110 and produces zero carbon oxide emissions compared to traditional fossil fuels. Due to its low boiling point, liquid ammonia is highly susceptible to flash boiling even at high ambient pressures under engine-like conditions. However, the characteristics of superheated ammonia spray are not fully understood due to the combined effects of bubble explosion in the near-field and strong aerodynamic interactions during its penetration process. In this study, the spray characteristics of ammonia under different fuel temperatures and ambient densities were investigated in a constant volume chamber to cover a wide range of superheat degrees. High speed diffused back-illumination method was adopted to measure both micro-and macroscopic features of ammonia spray. A non-dimensional analysis was established for the near-field characteristics to correlate critical factors to quantified bubble explosion intensity of ammonia as well as methanol and n-hexane for a comparison. It is found that both superheat degree and fuel viscosity play a significant role in the entire flashing region. For the far-field characteristics, the evolution of penetration is divided into three stages, and the dominant factor in each stage is investigated systematically. These experimental data would provide insightful information for understanding the breakup mechanism and developing simulation models of ammonia sprays.